Evapotranspiration and the crop coefficients of black bean (Phaseolus vulgaris) with weighing lysimeters in a subtropical region - JOSÉ ALEXANDER GIL-MARÍN; ALEJANDRO ZERMEÑO-GONZÁLEZ; MARÍA XIMENA CÓRDOVA-RODRÍGUEZ; HOMERO RAMÍREZ-RODRÍGUEZ; AARON ISAIN MELENDRES-ALVAREZ; LUIS SAMANIEGO MORENO; SASIROT KHAMKURE (Asian Journal of Agriculture, 2025)
Abstract. Gil-Marín JA, Zermeño-González A, Córdova-Rodríguez MX, Ramírez-Rodríguez H, Melendres-Alvarez AI, Moreno LS, Khamkure S. 2025. Evapotranspiration and the crop coefficients of black bean (Phaseolus vulgaris L.) with weighing lysimeters. Asian J Agric 9: 349-357. The water needs of a crop depend on the weather conditions, crop characteristics, and stage of development, which are represented by the crop coefficient (Kc), whose values change throughout the crop's stages of development. This understanding is the result of a meticulous research process, ensuring the reliability of these findings; knowing the crop evapotranspiration is essential to improving water use efficiency. This study aimed to determine the values of the crop evapotranspiration (ETc) and Kc for a black bean crop using a weighing lysimeter under greenhouse conditions. The research was conducted in the greenhouse of the graduate program in Tropical Agriculture at the University of Oriente (UDO), located on the Juanico Campus in Maturín, Monagas State, Venezuela, during the dry season from March to June 2020, on an Ultisol soil. The results showed that the bean's daily rate of evapotranspiration (ETc) was 3.16, 6.31, 8.37, and 4.80 mm day-1 for the initial growth, vegetative, flowering, and maturity stages, respectively. The evapotranspiration for the complete growing cycle was 458.31 mm, corresponding to a water volume of 4,583.10 m³ ha-1. The crop coefficient (Kc) for each development stage was 0.51 for the initial stage (10 days), 0.88 for the vegetative stages (35 days), 1.20 for the flowering stage (20 days), and 0.85 for the maturity stage (8 days).